A Modified Orthogonalization Minimization Algorithm for Millimeter Massive MIMO Communications - Mohammed, Yaseen Aiman; Mahmood, Anas L. (Proceedings (International Confernce on Computational Intelligence and Communication Networks), 2024)
Hybrid beamforming is a promising solution to reduce the complexity and cost of massive multiple-input multiple-output (MIMO) systems while maintaining high data rates comparable to digital beamforming. This study aims to develop a hybrid beamforming algorithm for multiuser Massive MIMO systems. The algorithm is designed to improve spectral efficiency and reduce computation time by utilizing discrete phase shifters in the Radio Frequency (RF) chains instead of continuous ones, lowering system costs. The methodology involves performing a literature review on the existing hybrid beamforming algorithms, deriving a new algorithm, and finally, applying it to numerical experiments, evaluating its performance against existing algorithms in terms of spectral efficiency and computation time. Results demonstrate that the proposed algorithm outperforms recent algorithms, achieving higher spectral efficiency and a significant decrease in computational demands.